FAKTOR - FAKTOR YANG MEMPENGARUHI KEPATUHAN IBU HAMIL DALAM PEMERIKSAAN KEHAMILAN DI KLINIK ROMANA TAHUN 2019 - HELENA FRANSYSCA (LP2MTBM MAKARIOZ, 2021)
This study aims to find out the factors that affect the mother's compliance in pregnancy examination at The Romana Clinic in2019. This type of research is descriptive with the design of survey research. Samples in this study as many as 60 peoplewith total sampling techniques. The results of this study showed that the compliance of mothers to check pregnancy basedon knowledge is good as many as 33 mothers (55.0%), get social support as many as 57 mothers (95.0%), givinginformation less 28 mothers (46.7%) and the interaction of health professionals is good i.e. 58 mothers (96.7%). It isrecommended for the Clinic to provide a clear explanation to pregnant women who conduct examinations so that pregnantwomen know the development and growth of babies in the womb and get antenatal services according to standards.